Future of the Past. Film and the Beginnings of Postmodern History - Rosenstone, Robert A. (Iluminace, 2004)
A study of the approach of film historians and theorists to the capture, representation and treatment of modern history. Postmodern Historiography.
Keywords: history and film; film historians; film theorists